Raoul Hausmann. Hyle in the rural architecture of Ibiza - Acilu, Aitor (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2015)
During his three-year stay in Ibiza, 1933-1936, Raoul Hausmann walked through some of the most characteristic locations of the island. His particular sensitivity, allowed him to recognise the value of the legacy of the material culture that remained on the rural houses of the island. This approach imbued an exhaustive analysis of the details of these constructions and the morphology of the landscape. Hausmann’s research was embodied in his diaries; small booklets turned into real sketchbooks. His drawings provide a unique look, focused on discovering the origins of those architectures of clear geometries and controlled proportions, created with certain spontaneity to respond to the needs of the human being, attending to their materials and construction techniques,. His discourse was developed in hundreds of typed pages and almost five hundred photographic negatives. The contact with the material culture of Ibiza, would certainly mean, the discovery of a myriad of intercultural relations between the elements of the rural houses of the island and other examples in the Mediterranean area. Haussmann discovered the universal character of this architecture; and so he discovered the true value of Hyle.